High-dose ascorbic acid synergizes with anti-PD1 in a lymphoma mouse model - Luchtel, Rebecca A. (Proc Natl Acad Sci U S A, 2020)
Major efforts are underway to identify agents that can potentiate effects of immune checkpoint inhibition. Here, we show that ascorbic acid (AA) treatment caused genomewide demethylation and enhanced expression of endogenous retroviral elements in lymphoma cells. AA also increased 5-hydroxymethylcytosine (5hmC) levels of CD8+ T cells and enhanced their cytotoxic activity in a lymphoma coculture system. High-dose AA treatment synergized with anti-PD1 therapy in a syngeneic lymphoma mouse model, resulting in marked inhibition of tumor growth compared with either agent alone. Analysis of the intratumoral epigenome revealed increased 5hmC with AA treatment, consistent with in vitro findings. Analysis of the tumor immune microenvironment revealed that AA strikingly increased intratumoral infiltration of CD8+ T cells and macrophages, suggesting enhanced tumor immune recognition. The combination treatment markedly enhanced intratumoral infiltration of macrophages and CD8+ T lymphocytes, granzyme B production by cytotoxic cells (cytotoxic T cells and natural killer cells), and interleukin 12 production by antigen-presenting cells compared with single-agent anti-PD1. These data indicate that AA potentiates anti-PD1 checkpoint inhibition through synergistic mechanisms. The study provides compelling rationale for testing combinations of high-dose AA and anti-PD1 agents in patients with aggressive B cell lymphoma as well as in preclinical models of other malignancies.